A national survey of surgical antibiotic prophylaxis in Turkey - Hosoglu, S; Sunbul, M; Erol, S; Altindis, M; Caylan, R; Demirdag, K; Dokucu, AI (Slack Inc, 2003)
OBJECTIVE: To assess the quality of antibiotic prophylaxis for clean and clean-contaminated elective surgical procedures. DESIGN: A cross-sectional, country-wide survey. SETTING: Thirty-six hospitals in 12 cities in Turkey. PARTICIPANTS: Four hundred thirty-nine surgeons from 6 different specialties who performed selected procedures of interest. METHODS: A random sample of surgeons from different hospitals was selected. A standardized data collection form was used to record the type of procedure, the names, doses, timing of the first doses, and duration of antibiotics, important decisive factors, and problems in the management of prophylactic antibiotic use for surgical procedures. RESULTS: Fifty-five percent of surgeons addressed completed the survey. For clean-contaminated procedures, 6% of surgeons did not use antibiotic prophylaxis, whereas 88% used more than a single dose. Inappropriate antibiotics were chosen for 32% of procedures. In 39% of procedures, the first dose of antibiotics was not administered during induction of anesthesia. Duration of prophylaxis was longer than 24 hours in 80% and longer than 48 hours in 46% of all procedures. Only 112 surgeons (2696) were using definitely appropriate prophylaxis in all ways. Multivariate analysis revealed that surgeons in university hospitals (OR, 2.353; CI95, 1.426-3.884; P = .001) and general surgeons (OR, 4.986; CI95, 2.890-8.604; P < .001) used antibiotic prophylaxis more appropriately. Patients not covered by health insurance (OR, 0.417; CI95, 0.225-0.772; P<.001) were associated with inappropriate prophylaxis. CONCLUSION: Given the high frequency of antibiotics prescribed for surgical prophylaxis in Turkey, adherence to surgical prophylaxis guidelines is urgently needed.
Keywords: Antimicrobial Prophylaxis; Wound-Infection; Hernia Repair; Guidelines; Risk; Hospitals; Surgery; Care